The Costs of Taxation and the Marginal Cost of Funds - Slemrod, Joel (IMF Working Papers; Working Paper ;, 1995)
It is argued that taxation causes three kinds of deadweight losses and two types of direct costs. The deadweight losses arise from substitution, evasion, and avoidance activities while the direct costs are administrative and compliance costs. Some of these social costs tend to be discontinuous and/or nonconvex. Because most models of taxation ignore some components of the social costs of taxation, their conclusions cannot be of a general nature. An alternative approach to policy evaluation is to rely on a marginal efficiency cost of funds rule which can indicate appropriate directions of reforms. The paper discusses its merits, applicability, and limitations, as well as its relationship to other concepts.